Community Satisfaction Analysis towards Corporate Social Responsibility Program of PT Kilang Pertamina Internasional Dumai Unit - Mukhammad Fatkhullah; Syauqiy Ridlo Robbiy; Iwed Mulyani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study measures the Community Satisfaction Index towards the Corporate Social Responsibility Program of PT Kilang Pertamina Internasional Dumai Unit (RU II Dumai) in 2022. The unit of analysis for this study is the beneficiaries of the CSR program consisting of the Tuna Fishermen Community, Palas Jaya Cultivation Community, and the Natural Farmer Community. Researchers use guidelines from the Ministry of Administrative and Bureaucratic Reform (PERMENPAN & RB) No. 14 of 2017 in compiling indicators to determine the value of the satisfaction index. The responses collected were then tabulated and analyzed using descriptive statistical analysis methods. The research results show that the Community Satisfaction Index for the Corporate Social Responsibility Program through 44 respondents is 3.39, or 84.68 after conversion. It can be concluded that the Community Satisfaction Index for the RU II Dumai CSR Program in 2022 is categorized as "Excellent" with an "A" grade. Based on data from the 14 processed elements, the lowest score for the element of response to input and suggestions from the public is 3.2 or 79.0 after conversion, which is in the range of 62.51-81.25 with a "B" grade. Therefore, companies need to increase responsiveness to input and suggestions from the community to develop CSR programs.